A Novel Algorithm for Effective Vibration Control of Portal Frames - Toloue, Iraj; Liew, Mohd Shahir; Harahap, Indra Sati Hamonangan; Lee, Hsiu Eik (ITB Journal Publisher, LPPM ITB, 2018)
Severe vibrations such as earthquakes threaten to demolish or cause damage to built structures during their lifetime. Mitigation of such damage can be done by using control devices such as actuators. In this paper, an algorithm is proposed to analyze the nonlinear behavior of a portal frame supported by an actuator. The results were compared with those for a frame without actuator. The algorithm was developed in accordance with the Timoshenko beam element theory. ANSYS verified the results for the cases of a frame supported by a damper element and a frame without actuator. The results support the efficiency of the algorithm in reducing frame vibration and top-node displacement.